Azienda Ospedaliero-Universitaria Meyer. Relazione Clinico-Scientifica 2007-2008-2009 - Sirianni, Luigi (Proceedings e report, 2010)
The clinical-scientific report 2007-2009 of the Meyer Hospital is the annotated description of the activities stemming from the two elements that make up the 'mission' of the structure: health care and research. It has been structured in such a way that the integration between these two functions emerges as an essential element for the pursuit of hospital excellence. For those working in the hospital the work undoubtedly represents a useful stimulus for meditation and self-assessment regarding the activities performed; at the same time it also offers an ulterior tool for making the Meyer better known beyond the hospital itself.